The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.30722/ijisme.30.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Argumentation in an Euclidean Geometry Context: A Case Study

Abstract: The research reported in this study examined the quality of argumentation of South African Grade 11 learners through the lens of Toulmin’s argument pattern (TAP). Very little research has quantified the argumentation of learners in mathematics across the school grades. The focus was on measuring the mathematical knowledge and quality of arguments formulated by learners as they engage in a reasoning task set in a Euclidean geometry investigative context. Mathematics education reform efforts have highlighted the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(35 reference statements)
0
1
1
Order By: Relevance
“…Apart from all that, many students are good at constructing arguments. The results differ from research by Shongwe (2022) which states that students are still categorized as low in constructing arguments because, in the arrangement of students' arguments, there are no rebuttals. Likewise, in research conducted by Andrea (2010), several groups of students and teachers used Toulmin argumentation stages where the results showed that Toulmin argumentation components in the form of claims, data, warrant, and backing could be demonstrated by students, but few could demonstrate rebuttal and qualifier (Soewardini et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Apart from all that, many students are good at constructing arguments. The results differ from research by Shongwe (2022) which states that students are still categorized as low in constructing arguments because, in the arrangement of students' arguments, there are no rebuttals. Likewise, in research conducted by Andrea (2010), several groups of students and teachers used Toulmin argumentation stages where the results showed that Toulmin argumentation components in the form of claims, data, warrant, and backing could be demonstrated by students, but few could demonstrate rebuttal and qualifier (Soewardini et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…Supporting this incident, research conducted by Basri et al (2019) also states that some students often do not understand the concept well and have difficulty understanding the entire information about the question, thus preventing students from carrying out proofs. This shows the inability of students to provide arguments and difficulty reaching higher levels of thinking (Shongwe, 2022).…”
Section: Introductionmentioning
confidence: 99%